An inerter enhanced floating floor structure for seismic hazard mitigation. (15th July 2022) - Cheng, Zhibao; Ma, Haomin; Shi, Zhifei; Jia, Gaofeng
Abstract: This paper proposes an inerter enhanced floating floor structure (In-FFS) for seismic hazard mitigation of building structures and the secondary systems. First, a one-dimensional inerter-based composite system is proposed. Equipping this inerter-based composite system on the traditional floating floor structure (FFS) leads to the proposed In-FFS. Second, modal participation property analysis is performed to investigate the dynamic performances of the In-FFS, including the mass reduction mechanism and the inerter enhancement effects. Third, time history analyses of three types of structures, i.e., the frame structure (FS), the FFS, and the proposed In-FFS, under scaled strong-motion earthquake records are conducted and their seismic performances are compared. Effects of the floating mass ratio, the inertance and damping on the seismic performance of the In-FFS are investigated. Further, genetic algorithm is used to optimize the parameters of the In-FFS to minimize the maximum responses of the entire system. While the FFS can suppress both the inter-story drift of the primary structure and the acceleration of the floated floors compared to the FS, the relative displacement between the primary structure and the floated floors are extremely large. Results from this study show that the In-FFS can not only reduce the relative displacement between the primary structure and the floated floor (e.g., by more than 40% w.r.t. those of the FFS) but also reduce the floor acceleration and the inter-story drift of the primary structure (e.g., by more than 20% and 10%, respectively). Highlights: An inerter enhanced floating floor structure (In-FFS) is proposed. Dynamic performances of the In-FFS are investigated. Time history results validate the superior performances of the In-FFS. Effects of the parameters of the In-FFS on its seismic performance are investigated. Genetic algorithm is used to optimize the parameters of the In-FFS.